2017
DOI: 10.1016/j.chemgeo.2017.03.020
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of oxygen isotope SIMS matrix effects in olivine samples: Correlation with sputter rate

Abstract: A B S T R A C TWe investigated the magnitude and reproducibility of instrumental mass-dependent fractionation of oxygen isotopes in secondary ion mass spectrometry (SIMS) analyses of olivine crystals of different major element chemistry (from Mg-rich to Fe-rich) in order to improve the accuracy of in-situ O-isotope measurements in geochemical/cosmochemical olivine samples. We found that oxygen isotope SIMS matrix effects are reproducible, and developed a model curve that can be used for correcting instrumental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
35
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 30 publications
3
35
0
Order By: Relevance
“…, Isa et al . ), this could significantly improve our understanding of what drives the first‐order differences of ~ 10–20‰ in bias magnitude between the end‐members of the dolomite–ankerite and magnesite–siderite solid‐solution series.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…, Isa et al . ), this could significantly improve our understanding of what drives the first‐order differences of ~ 10–20‰ in bias magnitude between the end‐members of the dolomite–ankerite and magnesite–siderite solid‐solution series.…”
Section: Resultsmentioning
confidence: 95%
“…, Isa et al . ). Nonetheless, what is apparent from the data at hand is that above a certain threshold Fe mass fraction, carbonate δ 18 O bias calibration curve shapes are strongly influenced by session‐specific differences in instrument tuning (reflected by the resulting pit morphologies/geometries).…”
Section: Resultsmentioning
confidence: 97%
“…In contrast, it may be preferable to analyze high‐FeO olivines with the RF source, although the Si ion yield is lower. In any case, as with Mg and O isotopic measurements in olivine, a comprehensive set of standards is needed to avoid artificial isotopic fractionations and to ensure high‐precision IMF corrections for Si isotopes.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, it has been shown that (i) IMF varies linearly with the mass‐to‐charge ratio of octahedral cations (e.g. Mn, Mg, Fe, Ti) as they impact the strength of the OH and OB bond for analyses of 2 H/ 1 H in micas and amphiboles and 11 B/ 10 B in tourmaline, (ii) IMF during 18 O/ 16 O analyses in silicates depends on the SiO 2 and FeO contents, (iii) IMF during 18 O/ 16 O analyses in carbonates depends on Fe, Mg, and Mn contents, and (iv) IMF during 30 Si/ 28 Si and 44 Ca/ 40 Ca analyses in CaO–MgO–Al 2 O 3 –SiO 2 (CMAS) glasses varies linearly with optical basicity . Thus, for a given isotopic system, it is often possible to build an empirical calibration from measurements of a limited number of well‐chosen standards, and interpolate IMF values for different (but related) compositions.…”
Section: Introductionmentioning
confidence: 99%
“…(, ), and Isa et al . (), in order to evaluate instrumental reproducibility as well as the behaviour of serpentine (a phyllosilicate) under the Cs + primary ion beam relative to other minerals commonly analysed by ion microprobes (nesosilicates). Olivine was chosen as a reference material because it has a chemical composition relatively similar to that of serpentine.…”
Section: Methodsmentioning
confidence: 99%